Analysis of Resistance Gene Diversity in the Intestinal Microbiome of Broilers from Two Types of Broiler Farms in Hebei Province, China - Chuncai Liang; Yujie Wei; Xiaolan Wang; Jinduo Gao; Huan Cui; Cheng Zhang; Juxiang Liu (MDPI AG, 2023)
The crucial reservoir of antibiotic resistance genes (ARGs) within the chicken intestinal microbiome poses a serious threat to both animal and human health. In China, the overuse of antibiotics has significantly contributed to the proliferation of ARGs in the chicken intestinal microbiome, which is a serious concern. However, there has been relatively little research on the diversity of resistance genes in the chicken intestinal microbiome since the implementation of the National Pilot Work Program for Action to Reduce the Use of Veterinary Antimicrobial Drugs in China. The objective of this study was to analyze the diversity of antibiotic resistance genes carried by the chicken intestinal microbiome in both standard farms (SFs), which implement antibiotic reduction and passed national acceptance, and nonstandard farms (NSFs), which do not implement antibiotic reductions, in Hebei Province. Fresh fecal samples of broiler chickens were collected from SFs (n = 4) and NSF (n = 1) and analyzed using high-throughput qPCR technology. Our findings revealed that all five farms exhibited a wide range of highly abundant ARGs, with a total of 201 ARGs and 7 MGEs detected in all fecal samples. The dominant ARGs identified conferred resistance to aminoglycosides, macrolide-lincosamide-streptomycin B (MLSB), and tetracycline antibiotics. Cellular protection mechanisms were found to be the primary resistance mechanism for these ARGs. The analysis of the co-occurrence network demonstrated a significant positive correlation between the abundance of MGEs and ARGs. The SF samples showed a significantly lower relative abundance of certain ARGs than the NSF samples (p < 0.05). The results of this study show that the abundance of ARGs demonstrated a downward trend after the implementation of the National Pilot Work Program for Action to Reduce the Usage of Veterinary Antimicrobial Drugs in Hebei Province, China.